Studi Eksperimen Pengaruh Jumlah Sudu Terhadap Kerja Turbin Angin Horisontal Berbasis NACA 4415 - MUSTAQIM, THORIQ (2016)
The use of wind energy is an effort to comply the electricity needs. Therefore, the conversion system of wind into electrical energy is very important to support it. This research discusses the system of horizontal axis wind turbine with various blades number (3, 4 and 5) referring to NACA 4415. This experiment has been performed in Pandansimo beach, Yogyakarta. The research was started by assembling all components of wind turbines such as tower, yaw drive, steering head and turbine blades. Blade components were made by iron plate with a thickness of 2 mm and diameter of 2.85 m. Data was collected by measured tool such as anemometer, digital tachometer and data logger. The anemometer was installed at the same height of wind turbine. Performance of wind turbine with-and-without load was investigated by measuring current, voltage, and power. The results show that, the wind speed affects the rotation of wind turbines. The higher wind speed the higher round wind turbines. Investigation of wind turbine without load generates the highest level of power when using 3 blades configuration. Whilst, the highest level of power for wind turbine with load can be achieved using 5 blades configuration. Besides, the construction of wind turbines with 5 blades also produces the highest power coefficient up to twice that of two other blade variations.